Early Release of Convicts - Milić, Ivan; Drakić, dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Summary: One of the modes of „release ahead of time“ from a penitentiary institution, or from a place of residence in which a convict may be serving his sentence, is early release. Early release can not be approved for every convict. There are exceptions to the rule that convicts are eligible for early release based on good behaviour. Early release may be granted by the director of the Administration for Execution of Prison Sentences or by a judge for enforcement of criminal sanctions.The author's attention in this paper is precisely the early release of convicts – those serving their sentence in penitentiary institutions as well as those serving them in their place of residence.